Innovative Design, Construction and Performance Evaluation of a Small Solar Timber Drying Kiln - Kumar, Shailendra; Ramkishore; Kandpal, R. P. (Indian Forester, 2015)
A semi-green house type improvised design prototype of solar timber drying kiln was designed and constructed at Forest Research Institute (F.R.I.), Dehradun (30.32Â° N, 78.03Â° E). Roof and side walls of the kiln were made of double glass glazing. The inclination angle of south facing roofs of the kiln was divided into two parts in order to provide sufficient heat to solar kiln in winters. Aluminium finning was done in kiln’s main flat plate solar collector made of G.I. (Galvanised Iron) sheet for efficient heat removal, which ran parallel to the roof. The air circulating fans were positioned to force air to flow from north to south direction. The design allowed the flowing air interact with Aluminium fins. The east and west walls of the kiln were also provided with inbuilt blackened G.I. sheet flat plate collectors to trap solar energy in early morning and late evening. Empty test runs in month of April, 2014 showed quick temperature rise in kiln especially in morning and evening, and maximum temperature of 98.6Â° C was achieved inside the kiln at 14:00 hrs. A test wood charge of 1 m3 teak wood of thickness 3.8 cm was dried from 70% to 11% MC (Moisture content) without any significant visible defects in 15 days.